2015
DOI: 10.1038/ncomms8086
|View full text |Cite
|
Sign up to set email alerts
|

CD11c-mediated deletion of Flip promotes autoreactivity and inflammatory arthritis

Abstract: Dendritic cells (DCs) are critical for immune homeostasis. To target DCs, we generated a mouse line with Flip deficiency in cells that express cre under the CD11c-promoter (CD11c-Flip-KO). CD11c-Flip-KO mice spontaneously develop erosive, inflammatory arthritis, resembling rheumatoid arthritis, which is dramatically reduced when these mice are crossed with Rag−/− mice. The CD8α+ DC subset is significantly reduced, along with alterations in NK cells and macrophages. Autoreactive CD4+ T cells and autoantibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(63 citation statements)
references
References 66 publications
3
60
0
Order By: Relevance
“…As such, c-FLIP expression may be central to the regulation of inflammatory versus tolerogenic DC function. This is consistent with findings in mice in which c-FLIP was deleted in DC, resulting in reduced numbers of DC, consistent with the requirement of c-FLIP for their survival [22]. Of particular interest was that these mice spontaneously developed autoreactive T cells and inflammatory arthritis.…”
Section: Discussionsupporting
confidence: 88%
“…As such, c-FLIP expression may be central to the regulation of inflammatory versus tolerogenic DC function. This is consistent with findings in mice in which c-FLIP was deleted in DC, resulting in reduced numbers of DC, consistent with the requirement of c-FLIP for their survival [22]. Of particular interest was that these mice spontaneously developed autoreactive T cells and inflammatory arthritis.…”
Section: Discussionsupporting
confidence: 88%
“…Although arthritis has not been examined in myeloid cell-specific FLIP-deficient mice, a study published in 2015 reported that targeted deletion of FLIP in both the CD8 + and CD11b − DC compartments of mice promotes the spontaneous development of an erosive inflammatory arthritis that resembles RA and is accompanied by the production of autoantibodies to joint antigens 100 . Prior to the onset of arthritis, DC populations (in particular CD8 + DCs) are substantially reduced in the thymus, spleen and lymph nodes 100 .…”
Section: Extrinsic Pathway Of Apoptosis In Ramentioning
confidence: 99%
“…Prior to the onset of arthritis, DC populations (in particular CD8 + DCs) are substantially reduced in the thymus, spleen and lymph nodes 100 . Although DC-specific FLIP -knockout mice are lymphopenic, autoreactive CD4 + T cells are detected, suggesting that these cells might participate in the propagation of arthritis 100 .…”
Section: Extrinsic Pathway Of Apoptosis In Ramentioning
confidence: 99%
“…Loss of FLIP in the conventional CD8 + and CD11b − dendritic cell compartments ( CD11c cre Flip flox/flox ) promotes spontaneous development of an erosive inflammatory arthritis accompanied by autoantibodies to joint antigens that resembles another autoimmune disorder, rheumatoid arthritis [131]. Prior to the onset of arthritis, the dendritic cell populations, CD8 + dendritic cells in particular, are significantly decreased in the thymus, spleen, and lymph nodes [131].…”
Section: Programmed Cell Death Pathways In Dendritic Cells and Macmentioning
confidence: 99%
“…Prior to the onset of arthritis, the dendritic cell populations, CD8 + dendritic cells in particular, are significantly decreased in the thymus, spleen, and lymph nodes [131]. Although CD11c cre Flip flox/flox mice are lymphopenic, autoreactive CD4 + T cells are detected and correlate with reduced regulatory T cell numbers [131]. Another group reported that CD11c cre Flip flox/flox mice develop neutrophilia, owing to excess availability of G-CSF, and splenomegaly.…”
Section: Programmed Cell Death Pathways In Dendritic Cells and Macmentioning
confidence: 99%